2014
DOI: 10.3758/s13420-014-0135-0
|View full text |Cite
|
Sign up to set email alerts
|

Do monkeys choose to choose?

Abstract: There is empirical and anecdotal support that choice is preferred by humans. Previous research has demonstrated that this preference extends to nonhuman animals, but it remains largely unknown whether animals will actively seek out or prefer opportunities to choose. Here we explored the issue of whether capuchin and rhesus monkeys will choose to choose. We used a modified version of the SELECT task – a computer program in which monkeys can choose the order of completion of various psychomotor and cognitive tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 22 publications
2
37
2
Order By: Relevance
“…We found no performance differences when monkeys chose to complete a task (in binary and trinary choice sets) versus when it was assigned to them (in forced Training trials). This finding was inconsistent with previous work using the SELECT battery with rhesus monkeys (Washburn et al, 1991) and capuchin monkeys (Perdue et al, 2014). However, unlike in those previous task batteries, the current task options were limited to relatively few choices (two tasks versus up to five tasks).…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…We found no performance differences when monkeys chose to complete a task (in binary and trinary choice sets) versus when it was assigned to them (in forced Training trials). This finding was inconsistent with previous work using the SELECT battery with rhesus monkeys (Washburn et al, 1991) and capuchin monkeys (Perdue et al, 2014). However, unlike in those previous task batteries, the current task options were limited to relatively few choices (two tasks versus up to five tasks).…”
Section: Discussioncontrasting
confidence: 89%
“…For example, monkeys performed better on some tasks when they had chosen them (i.e., choice trials) than when the same tasks were simply assigned to them (i.e., forced trials). Later work replicated and extended this result with capuchin monkeys (Beran, Klein, Evans, Antworth, & Chan, 2007;Perdue, Evans, Washburn, Rumbaugh, & Beran, 2014).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Westlund (2012) proposed that the use of preference tests may also result in a reduction in the need for fluid and food restriction in laboratory-housed primates. Finally, given the fact that nonhuman primates have been shown to prefer choice conditions (Perdue et al, 2014), the simple act of choosing a reinforcer may, in itself, provide a welfare benefit to animals.…”
Section: Discussionmentioning
confidence: 99%
“…Sambrook and Buchanan-Smith suggest that for captive animal enrichment, controllability appears more important than complexity although they focus on the characteristics of novel objects. Furthermore, Perdue, Evans, Washburn, Rumbaugh, and Beran (2014) demonstrated that capuchin monkeys and rhesus macaques "choose to choose," in the sense that they will choose the order in which they complete various psychomotor and cognitive tasks on a computerized system.…”
Section: Future Directionsmentioning
confidence: 99%